Laser Glass

By rationally designing the components and molar percentage of laser glass, optimizing its network structure and chemical bonds, the problem of insufficient thermal conductivity and expansion coefficient of erbium laser glass is solved, and laser glass with high thermal conductivity, low expansion coefficient and long radiation life is achieved, improving laser gain performance and equipment stability.

CN119774876APending Publication Date: 2025-04-08CDGM GLASS LLC
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411788490.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The thermal conductivity and expansion coefficient of existing erbium laser glasses are rarely studied, and it is difficult to meet the thermal performance requirements of high-power lasers.

Method used

By rationally designing the components of laser glass, it contains P2O5, B2O3, Al2O3, Na2O, MgO, Yb2O3, Er2O3, Cr2O3 and other components, and controls its molar percentage range to optimize the network structure and chemical bonds of the glass, improve thermal conductivity and reduce expansion coefficient.

Benefits of technology

The high thermal conductivity and low linear expansion coefficient of laser glass are achieved, the radiation life is extended, the laser gain performance is improved, and the equipment stability and laser quality of laser glass are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174713980000081
    Figure BDA0005174713980000081
  • Figure BDA0005174713980000082
    Figure BDA0005174713980000082
  • Figure BDA0005174713980000101
    Figure BDA0005174713980000101
Patent Text Reader

Abstract

The present invention provides a laser glass with higher thermal conductivity and lower linear expansion coefficient. The laser glass, whose components are expressed in molar percentage, contains: P2O5: 50.0-59.0%; B2O3: 7.8-20.0%; Al2O3: 5.0-12.0%; Na2O: 0.5-9.0%; MgO: 0.5-6.0%; Yb2O3: 5.0-9.6%; Er2O3: 0.03-0.6%; Cr2O3: 0.04-0.5%. Through reasonable component design, the laser glass obtained by the present invention has a lower linear expansion coefficient and higher thermal conductivity, and at the same time has a longer radiation life, which is beneficial to the improvement of laser gain performance, can improve the thermal properties of laser glass, reduce or avoid damage and cracking of laser glass during operation, and optimize the equipment stability and laser quality of laser glass in high-power or continuous output scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to laser glass, in particular to laser glass with higher thermal conductivity and lower expansion coefficient. Background Art

[0002] Laser technology is one of the indispensable technologies for the survival and development of human intelligent society. Among all kinds of lasers, solid lasers have the characteristics of stable performance, small size and compact design. Erbium ion solid lasers can produce lasers in the 1.5μm or 3μm band. Among them, the 1.5μm band laser has been widely used in optical communication, laser ranging and other fields due to its strong ability to penetrate smoke, good compatibility with communication networks and eye safety. The pumping source of the xenon lamp pumped erbium glass laser is a xenon lamp. The design of the xenon lamp pumped erbium laser glass laser resonator and laser cavity follows the traditional neodymium glass laser system. It has the advantages of high stability, low cost, mature and simple system design, etc. It has a wide range of applications, especially in the fields of long-distance detection and laser beauty.

[0003] When the luminescent material is excited by the excitation light, the number of particles in the excited state is relatively large at the beginning. The luminescent particles emit fluorescence through radiation transition and return to the ground state. As the excitation light is removed, the number of particles in the excited state decreases, and the luminescence becomes weaker and weaker. This process of decreasing luminescence intensity is called fluorescence decay. The radiation lifetime is the lifetime of the particles in the excited state, which reflects the number of luminescent particles in the excited state. The longer the radiation lifetime, the more particles in the excited state. It has an important influence on the laser gain performance and is one of the key spectral parameters of laser glass. In order to further improve the performance of erbium laser glass, it is of great significance to develop erbium laser glass with a long radiation lifetime.

[0004] Erbium laser glass serves in laser systems, and its thermal conductivity and expansion coefficient are very important. High thermal conductivity helps erbium laser glass dissipate heat quickly to avoid heat accumulation, which causes laser beam distortion and even device damage; low expansion coefficient can avoid the problem of erbium laser glass breaking and being damaged due to volume change caused by temperature rise during service, but there is currently little research on the thermal conductivity and expansion coefficient of erbium laser glass. With the development trend of increasing laser application power, it is of great significance to conduct research on the thermal properties of erbium laser glass and develop erbium laser glass products with high thermal conductivity and low expansion coefficient. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a laser glass with higher thermal conductivity and lower linear expansion coefficient.

[0006] The technical solution adopted by the present invention to solve the technical problem is:

[0007] Laser glass, whose components are expressed in molar percentage, contains: P2O5: 50.0~59.0%; B2O3: 7.8~20.0%; Al2O3: 5.0~12.0%; Na2O: 0.5~9.0%; MgO: 0.5~6.0%; Yb2O3: 5.0~9.6%; Er2O3: 0.03~0.6%; Cr2O3: 0.04~0.5%.

[0008] Furthermore, the laser glass, whose components are expressed in molar percentage, also contains: CeO2: 0-1.0%; and / or Li2O: 0-4.5%; and / or K2O: 0-5.0%; and / or CaO: 0-3.7%; and / or Nb2O5: 0-1.45%; and / or La2O3: 0-0.8%; and / or Sb2O3: 0-0.7%.

[0009] Laser glass, whose components are expressed in molar percentage, consists of P2O5: 50.0~59.0%; B2O3: 7.8~20.0%; Al2O3: 5.0~12.0%; Na2O: 0.5~9.0%; MgO: 0.5~6.0%; Yb2O3: 5.0~9.6%; Er2O3: 0.03~0.6%; Cr2O3: 0.04~0.5%; CeO2: 0~1.0%; Li2O: 0~4.5%; K2O: 0~5.0%; CaO: 0~3.7%; Nb2O5: 0~1.45%; La2O3: 0~0.8%; Sb2O3: 0~0.7%.

[0010] Furthermore, the components of the laser glass are expressed in molar percentage, wherein: P2O5 / B2O3 is 2.6-7.3, preferably P2O5 / B2O3 is 2.8-7.0, and more preferably P2O5 / B2O3 is 3.0-6.7.

[0011] Furthermore, the components of the laser glass are expressed in molar percentage, wherein: (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is 2.0-8.0, preferably (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is 4.6-7.4, and more preferably (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is 5.5-7.4.

[0012] Furthermore, the components of the laser glass are expressed in molar percentage, wherein: (Nb2O3+Cr2O3) / (MgO+CaO) is 0.06~0.64, preferably (Nb2O3+Cr2O3) / (MgO+CaO) is 0.12~0.35, and more preferably (Nb2O3+Cr2O3) / (MgO+CaO) is 0.25~0.33.

[0013] Furthermore, the laser glass, wherein the components are expressed in molar percentage, wherein: P2O5: 55.8-58.4%, preferably P2O5: 56.4-58.0%; and / or B2O3: 8.0-18.9%, preferably B2O3: 8.0-15.3%; and / or Al2O3: 5.3-10.0%, preferably Al2O3: 6.8-10.0%; and / or Na2O: 1.5-8.9%, preferably Na2O: 2.1-8.0%; and / or MgO: 1.2-5.8%, preferably MgO: 1.5-4.7%; and / or Yb2O3: 7.5-9.6%, preferably Yb2O3: 7.7-9.2%; and / or Er2O3: 0.03-0.25%, preferably Er2O3: 0.04-0.22%; and / or or Cr2O3: 0.04-0.15%, preferably Cr2O3: 0.04-0.12%; and / or CeO2: 0.05-0.6%, preferably CeO2: 0.13-0.53%; and / or Li2O: 0-3.0%, preferably Li2O: 1.3-3.0%; and / or K2O: 0-4.0%, preferably K2O: 0-3.0%; and / or CaO : 0~1.5%, preferably CaO: 0.2~1.0%; and / or Nb2O5: 0.25~0.75%, preferably Nb2O5: 0.41~0.73%; and / or La2O3: 0.12~0.32%, preferably La2O3: 0.15~0.31%; and / or Sb2O3: 0~0.33%, preferably Sb2O3: 0.01~0.19%.

[0014] Furthermore, the radiation lifetime τ of the laser glass rad is 8.4 ms or more, preferably 10.4 ms or more, more preferably 11.2 ms or more, and further preferably 11.2 to 13.7 ms; and / or the stimulated emission cross section σ em 5.8×10 -21 cm 2 Above, preferably 6.8×10 -21 cm 2 More preferably, 7.1×10 -21 cm 2 More preferably, 7.1×10 -21 cm 2 ~9.7×10 -21 cm 2 ; and / or thermal conductivity λ 90℃ 0.55 W / (m*K) or more, preferably 0.63 W / (m*K) or more, more preferably 0.67 W / (m*K) or more, and further preferably 0.67 to 0.71 W / (m*K); and / or linear expansion coefficient α20~300℃ 7.7×10 -6 / K or less, preferably 7.5×10 -6 / K or less, more preferably 6.1×10 -6 / K~7.5×10 -6 / K.

[0015] A laser contains the laser glass.

[0016] The beneficial effects of the present invention are as follows: through reasonable component design, the laser glass obtained by the present invention has a lower linear expansion coefficient and a higher thermal conductivity, and at the same time has a longer radiation life, which is beneficial to improving the laser gain performance, and can improve the thermal properties of the laser glass, reduce or avoid damage and cracking of the laser glass during operation, and optimize the equipment stability and laser quality of the laser glass in high-power or continuous output scenarios. DETAILED DESCRIPTION

[0017] The following is a detailed description of the embodiments of the laser glass of the present invention. However, the present invention is not limited to the embodiments described below and can be implemented with appropriate changes within the scope of the purpose of the present invention. In addition, although there are cases where the repeated description is appropriately omitted, the main purpose of the invention is not limited thereto. In the following content, the laser glass of the present invention is sometimes referred to as glass.

[0018] [Laser Glass]

[0019] The following is an explanation of the range of each component (ingredient) of the laser glass of the present invention. In the present invention, unless otherwise specified, the content, total content, and combined content of each component are all expressed in mole percentage (mol%), that is, the content, total content, and combined content of each component are expressed in mole percentage relative to the total amount of glass material converted into an oxide composition. Here, the "composition converted into oxides" means that when oxides, complex salts, hydroxides, etc. used as raw materials for the laser glass components of the present invention decompose and transform into oxides when melted, the total molar amount of the oxide material is taken as 100%.

[0020] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0021] Compared with other 1.5μm lasers (such as semiconductor lasers and lamp-pumped Er:YAG lasers), lasers based on erbium phosphate laser glass gain media have the characteristics of small size, high efficiency, good stability, and low price, and have attracted widespread attention. 3+ It has weak absorption in the visible light band, while Yb 3+ It has strong absorption in the 800-1100nm band, and Yb 3+ Xiang Er 3+ The energy transfer efficiency is high, so the present invention adopts Yb 3+ In order to better absorb the pump light, the present invention uses Cr 3 + Co-doped as Yb 3+ The second sensitizing ion can use the energy in the visible light band for pumping. 3+ , Yb 3+ Cr 3+ During the xenon lamp pumping process of co-doped phosphate laser glass, Cr 3+ Absorbing pump light transitions to 4 T2 level, Yb 3+ Except for a small amount of direct excitation in the near-infrared region, a large amount of Yb 3+ The excitation is mainly through Cr 3+ of 4 T2 energy level and Yb 3+ of 2 F 7 / 2 The energy transfer channel between energy levels is completed, Er 3+ The excitation is mainly through Yb 3+ →Er 3+ Energy transfer is completed. Under xenon lamp pumping, compared with single erbium-doped phosphate glass, Er 3 + , Yb 3+ Cr 3+ Co-doped phosphate laser glass can achieve a significant increase in the output energy of free-oscillation lasers.

[0022] <Essential Components and Optional Components>

[0023] P2O5 is used as the main glass network former in the present invention, but too high a content of P2O5 will cause the glass network structure to transform into a layered (or chain) structure, increase the linear expansion coefficient of the glass, and deteriorate the chemical stability. Therefore, the content of P2O5 in the present invention is 50.0-59.0%, preferably 55.8-58.4%, and more preferably 56.4-58.0%.

[0024] B2O3 is a network former component of glass. Controlling the content of B2O3 in borophosphate can achieve regulation of glass network structure and optimize the linear expansion coefficient. With an appropriate increase in B2O3, the linear expansion coefficient of glass can be reduced. A certain amount of B2O3 can form BPO4 groups in the glass, transforming the original layered (or chain-like) structure of the phosphate into a frame-like structure, making the glass network structure more stable. However, excessive B2O3 will make the glass easy to phase separate and the chemical stability of the glass will deteriorate. Therefore, the content of B2O3 is 7.8-20.0%, preferably 8.0-18.9%, and more preferably 8.0-15.3%.

[0025] After extensive research, the inventors found that controlling the ratio of the glass network former components P2O5 and B2O3 in the glass can affect the glass network structure, thereby changing the linear expansion coefficient of the glass. In some embodiments, preferably P2O5 / B2O3 is in the range of 2.6 to 7.3, more preferably P2O5 / B2O3 is in the range of 2.8 to 7.0, and further preferably P2O5 / B2O3 is in the range of 3.0 to 6.7, which is beneficial to improving the stability of the glass while obtaining a lower linear expansion coefficient.

[0026] As a network intermediate, Al2O3 exhibits two characteristics: glass former and glass modifier. Aluminum can form aluminum-oxygen tetrahedrons with double-bonded oxygen in glass, which can improve the thermal and chemical stability of glass. However, excessive Al2O3 will reduce the stimulated emission cross section of laser glass. In the present invention, the content of Al2O3 is 5.0-12.0%, preferably 5.3-10.0%, and more preferably 6.8-10.0%.

[0027] Alkali metal oxides (alkali metal oxides include one or more of Li2O, Na2O, and K2O) are the outer bodies of the glass network, which can reduce the viscosity of the glass during high-temperature melting and lower the melting temperature. However, too much alkali metal oxide content will increase the crystallization and phase separation tendency of the glass and reduce the chemical stability of the glass; too little alkali metal oxide content will make the glass too viscous and difficult to melt. In order to achieve the excellent effect of the present invention, the content of Li2O is preferably 0-4.5%, more preferably 0-3.0%, and further preferably 1.3-3.0%; the content of Na2O is preferably 0.5-9.0%, more preferably 1.5-8.9%, and further preferably 2.1-8.0%; the content of K2O is preferably 0-5.0%, more preferably 0-4.0%, and further preferably 0-3.0%.

[0028] Sb2O3 is a clarifying agent that can make it easier to eliminate bubbles in glass. In the present invention, the content of Sb2O3 is 0 to 0.7%, preferably 0 to 0.33%, and more preferably 0.01 to 0.19%.

[0029] In the glass of the present invention, La2O3 can improve the chemical stability of the glass and reduce the linear expansion coefficient, but La 3+ The field is strong, the radius is large, and it is easy to accumulate and reduce the range of glass generation. When it is contained in large quantities, the glass is easy to crystallize. In the present invention, the content of La2O3 is 0-0.8%, preferably 0.12-0.32%, and more preferably 0.15-0.31%.

[0030] The laser emission center of the glass of the present invention is Er 3+ The Er2O3 content has an important influence on the laser performance of laser glass. The increase in Er2O3 content can increase the number of luminescence centers, but excessive Er2O3 will cause concentration quenching, resulting in a decrease in the stimulated emission cross section and radiation lifetime. In the present invention, the Er2O3 content is 0.03-0.6%, preferably 0.03-0.25%, and more preferably 0.04-0.22%.

[0031] Yb 3+ It is the sensitizer of the laser glass of the present invention, responsible for transferring the energy of the pump light to Er 3+ The increase of Yb2O3 content is conducive to the energy transfer to Er 3+ However, excessive Yb2O3 will cause concentration quenching, and the glass melting viscosity will increase, making glass melting difficult. In the present invention, the content of Yb2O3 is 5.0-9.6%, preferably 7.5-9.6%, and more preferably 7.7-9.2%.

[0032] In the present invention, Cr 3+ Co-doped as Yb 3+ The second sensitizer can use the visible light band energy for pumping and then transfer the energy to Yb 3+ An appropriate amount of Cr2O3 is beneficial to improving the glass pumping efficiency, but an excessive amount will lead to concentration quenching. In the present invention, the content of Cr2O3 is 0.04-0.5%, preferably 0.04-0.15%, and more preferably 0.04-0.12%. Chromium ions in glass are not only Cr 3+ The state exists and may also be Cr 2+ Status appears, Cr 2+ The intrinsic absorption band of ions and Yb 3+ The emission bands overlap, increasing the self-absorption loss. It is necessary to control the Cr content in the glass. 2+ The content.

[0033] The cerium ion in CeO2 is tetravalent, which partially transforms into trivalent cerium during the smelting process, providing a certain oxidizing atmosphere and inhibiting the divalent Cr that is not conducive to laser performance. 2+Ions. An appropriate amount of CeO2 can also clarify the glass, but an excessive amount will cause serious coloring of the glass. In the present invention, the content of CeO2 is 0 to 1.0%, preferably 0.05 to 0.6%, and more preferably 0.13 to 0.53%.

[0034] After extensive research, the inventors found that the transition process of the radiation transition center in the glass is affected by the ion field strength environment and the glass network structure. By adjusting the ratio of Sb2O3+CeO2 to Cr2O3, the transition center Cr 3+ Field strength environment; by adjusting Al2O3 / B2O3 to change the glass network structure; the combined effect of the two affects Cr 3+ The pumping process and the energy transfer process achieve the effect of increasing the radiation lifetime of the glass. Therefore, in some embodiments, it is preferred that (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is in the range of 2.0 to 8.0, more preferably (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is in the range of 4.6 to 7.4, and further preferably (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is in the range of 5.5 to 7.4, which is beneficial to increase the radiation lifetime of the laser glass. In some embodiments, when the (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 in the glass meets the above range, the obtained laser glass radiation lifetime (τ rad ) is preferably 8.4 ms or more, and more preferably the radiation lifetime (τ rad ) is 10.4 ms or more, and the radiation lifetime (τ rad ) is above 11.2ms.

[0035] Alkaline earth metal oxides MgO and CaO can improve the physical and chemical properties of glass, but excessive inclusion will make glass melting difficult. Therefore, the content of MgO is 0.5-6.0%, preferably 1.2-5.8%, more preferably 1.5-4.7%; the content of CaO is 0-3.7%, preferably 0-1.5%, more preferably 0.2-1.0%.

[0036] An appropriate amount of Nb2O5 has the effect of increasing the glass dispersion coefficient and improving the chemical stability of the glass, but excessive Nb2O5 will reduce the glass vitrification property, easily cause crystallization, and increase the difficulty of melting. In the present invention, the content of Nb2O5 is 0 to 1.45%, preferably 0.25 to 0.75%, and more preferably 0.41 to 0.73%.

[0037] After extensive research, the inventors have found that in some embodiments, by controlling the (Nb2O3+Cr2O3) / (MgO+CaO) in the glass within the range of 0.06 to 0.64, the network structure and chemical bond strength of the glass can be changed, thereby improving the thermal conductivity of the glass. Therefore, it is preferred that (Nb2O3+Cr2O3) / (MgO+CaO) is 0.06 to 0.64, more preferably (Nb2O3+Cr2O3) / (MgO+CaO) is 0.12 to 0.35, and further preferably (Nb2O3+Cr2O3) / (MgO+CaO) is 0.25 to 0.33. In some embodiments, when the (Nb2O3+Cr2O3) / (MgO+CaO) in the glass satisfies the above range, the thermal conductivity (λ 90℃ ) is preferably 0.55 W / (m*K) or more, and more preferably the thermal conductivity (λ 90℃ ) is 0.63W / (m*K) or more, and the thermal conductivity (λ 90℃ ) is above 0.67W / (m*K).

[0038] <Components that should not be contained>

[0039] The glass of the present invention does not contain compounds of lead, cadmium, arsenic, etc., so as to be environmentally friendly and can be widely used in the fields of laser radar, optical communication, laser ranging, medical equipment, etc.

[0040] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the laser glass of the present invention; however, as raw materials and / or equipment for producing laser glass, there may be certain impurities or components that are not intentionally added, which may be contained in small amounts or trace amounts in the final laser glass, and this situation is also within the scope of protection of the patent of this invention.

[0041] Next, the properties of the laser glass of the present invention will be described.

[0042] <Laser performance—radiation lifetime, stimulated emission cross section>

[0043] Laser performance can be obtained based on Judd-Oflet theory and Fuchtbauer-Ladenburg theory. Discussions on Judd-Oflet theory and Fuchtbauer-Ladenburg theory can be found in E. Desurvire, Erbium Doped Fiber Amplifiers, John Wiley and Sons (1994). Judd-Oflet theory and Fuchtbauer-Ladenburg theory evaluate laser performance based on fluorescence emission curves. In this paper, the fluorescence emission spectrum excited by 460nm wavelength was measured using FluoroLog-3 fluorescence spectrometer.

[0044] For erbium laser glasses, the stimulated emission cross section and radiation lifetime performance are usually calculated using the Judd-Oflet theory combined with the Fuchtbauer-Ladenburg theory. A detailed description is provided in Hu Lili et al., Laser Glass and Applications, Shanghai Science and Technology Press (2019), which is incorporated herein by reference. MD Shinn et al., Optical transitions of Er 3+ ions of fluorozirconate glass, Physical Review B (1983), which is incorporated herein by reference.

[0045] Radiative lifetime (τ rad ) is determined by the following formula (1):

[0046]

[0047] Where A[(S,L)J; ​​(S′,L′)J′] is the spontaneous radiation relaxation rate of the electric dipole absorption transition from the initial state (S,L)J to the final state (S′,L′)J′, which can be calculated by the Judd-Oflet theory.

[0048] The stimulated emission cross section is determined by the following formula (2):

[0049]

[0050] Where I(λ) is the fluorescence emission curve obtained by fluorescence spectrophotometer test, and A is the probability of spontaneous radiation transition between upper and lower energy levels.

[0051] In some embodiments, the radiation lifetime (τ rad ) is 8.4 ms or more, preferably 10.4 ms or more, more preferably 11.2 ms or more, and further preferably 11.2 to 13.7 ms.

[0052] In some embodiments, the stimulated emission cross section (σ) of the laser glass of the present invention is em ) is 5.8×10 -21 cm 2 Above, preferably 6.8×10 -21 cm 2 More preferably, 7.1×10 -21 cm 2 More preferably, 7.1×10 -21 cm 2 ~9.7×10 -21 cm 2 .

[0053] <Thermal conductivity>

[0054] The present invention uses the NETZSCH LFA467 flash thermal conductivity instrument to test the thermal conductivity (λ 90℃ ), the test method is based on the national standard "GB / T 22588-2008".

[0055] In some embodiments, the thermal conductivity (λ 90℃ ) is 0.55 W / (m*K) or more, preferably 0.63 W / (m*K) or more, more preferably 0.67 W / (m*K) or more, and further preferably 0.67 to 0.71 W / (m*K).

[0056] <Linear expansion coefficient>

[0057] The present invention uses the NETZSCH DIL402C thermal expansion instrument to test the linear expansion coefficient (α 20~300℃ ), and the test method is based on the national standard "GB / T 7320-2008". In the present invention, the linear expansion coefficient is sometimes referred to as the expansion coefficient.

[0058] In some embodiments, the linear expansion coefficient (α 20~300℃ ) is 7.7×10 -6 / K or less, preferably 7.5×10 -6 / K or less, more preferably 6.1×10 -6 / K~7.5×10 -6 / K.

[0059] [Manufacturing method of laser glass]

[0060] The manufacturing method of the laser glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, composite salts (such as carbonates, nitrates, sulfates, phosphates, metaphosphates, etc.), boric acid, etc. as raw materials, and after mixing according to conventional methods, the prepared furnace materials are put into a melting furnace (such as a quartz crucible) at 1200-1300°C for melting, and after clarification and homogenization, the temperature is lowered to obtain a homogeneous molten glass without bubbles and undissolved substances, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.

[0061] [Laser]

[0062] The laser glass of the present invention can be used in various types of lasers due to its excellent performance, and can be widely used in laser radar, optical communication, laser ranging, medical equipment and other fields.

[0063] Example

[0064] In order to further clearly illustrate and describe the technical solutions of the present invention, the following non-limiting examples are provided. The present invention has made many efforts to ensure the accuracy of the numerical values, but some errors and deviations must be considered.

[0065] In the present embodiments E1 to E29, the manufacturing method of the present invention is used to obtain the laser glasses shown in Tables 1 to 4. In addition, the characteristics of each laser glass are measured by the testing method of the present invention, and the measurement results are shown in Tables 1 to 4.

[0066] Table 1.

[0067]

[0068]

[0069] Table 2.

[0070]

[0071] Table 3.

[0072]

[0073]

[0074] Table 4.

[0075]

[0076]

Claims

1. Laser glass, characterized in that: Its components, expressed in molar percentage, include: P2O5: 50.0-59.0%; B2O3: 7.8-20.0%; Al2O3: 5.0-12.0%; Na2O: 0.5-9.0%; MgO: 0.5-6.0%; Yb2O3: 5.0-9.6%; Er2O3: 0.03-0.6%; Cr2O3: 0.04-0.5%.

2. The laser glass according to claim 1, characterized in that: Its components, expressed in molar percentage, also contain: CeO2: 0-1.0%; and / or Li2O: 0-4.5%; and / or K2O: 0-5.0%; and / or CaO: 0-3.7%; and / or Nb2O5: 0-1.45%; and / or La2O3: 0-0.8%; and / or Sb2O3: 0-0.7%.

3. Laser glass, characterized in that: Its components are expressed in molar percentage, consisting of P2O5: 50.0~59.0%; B2O3: 7.8~20.0%; Al2O3: 5.0~12.0%; Na2O: 0.5~9.0%; MgO: 0.5~6.0%; Yb2O3: 5.0~9.6%; Er2O3: 0.03~0.6%; Cr2O3: 0.04~0.5%; CeO2: 0~1.0%; Li2O: 0~4.5%; K2O: 0~5.0%; CaO: 0~3.7%; Nb2O5: 0~1.45%; La2O3: 0~0.8%; Sb2O3: 0~0.7%.

4. The laser glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, wherein: P2O5 / B2O3 is 2.6-7.3, preferably P2O5 / B2O3 is 2.8-7.0, and more preferably P2O5 / B2O3 is 3.0-6.

7.

5. The laser glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, wherein: (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is 2.0-8.0, preferably (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is 4.6-7.4, and more preferably (Sb2O3+CeO2) / Cr2O3+Al2O3 / B2O3 is 5.5-7.

4.

6. The laser glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, wherein: (Nb2O3+Cr2O3) / (MgO+CaO) is 0.06-0.64, preferably (Nb2O3+Cr2O3) / (MgO+CaO) is 0.12-0.35, and more preferably (Nb2O3+Cr2O3) / (MgO+CaO) is 0.25-0.

33.

7. The laser glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, wherein: P2O5: 55.8-58.4%, preferably P2O5: 56.4-58.0%; and / or B2O3: 8.0-18.9%, preferably B2O3: 8.0-15.3%; and / or Al2O3: 5.3-10.0%, preferably Al2O3: 6.8-10.0%; and / or Na2O: 1.5-8.9%, preferably Na2O: 2.1-8.0%; and / or MgO: 1.2-5.8%, preferably MgO: 1.5-4.7%; and / or Yb2O3: 7.5-9.6%, preferably Yb2O3: 7.7-9.2%; and / or Er2O3: 0.03-0.25%, preferably Er2O3: 0.04-0.22%; and / or Cr2O3 : 0.04~0.15%, preferably Cr2O3: 0.04~0.12%; and / or CeO2: 0.05~0.6%, preferably CeO2: 0.13~0.53%; and / or Li2O: 0~3.0%, preferably Li2O: 1.3~3.0%; and / or K2O: 0~4.0%, preferably K2O: 0~3.0%; and / or CaO: 0~1.5%, preferably CaO: 0.2~1.0%; and / or Nb2O5: 0.25~0.75%, preferably Nb2O5: 0.41~0.73%; and / or La2O3: 0.12~0.32%, preferably La2O3: 0.15~0.31%; and / or Sb2O3: 0~0.33%, preferably Sb2O3: 0.01~0.19%.

8. The laser glass according to any one of claims 1 to 3, characterized in that: The radiation lifetime τ of the laser glass rad is 8.4 ms or more, preferably 10.4 ms or more, more preferably 11.2 ms or more, and further preferably 11.2 to 13.7 ms; and / or the stimulated emission cross section σ em 5.8×10 -21 cm 2 Above, preferably 6.8×10 -21 cm 2 More preferably, 7.1×10 -21 cm 2 More preferably, 7.1×10 -21 cm 2 ~9.7×10 -21 cm 2 ; and / or thermal conductivity λ 90℃ 0.55 W / (m*K) or more, preferably 0.63 W / (m*K) or more, more preferably 0.67 W / (m*K) or more, and further preferably 0.67 to 0.71 W / (m*K); and / or linear expansion coefficient α 20~300℃ 7.7×10 -6 / K or less, preferably 7.5×10 -6 / K or less, more preferably 6.1×10 -6 / K~7.5×10 -6 / K.

9. A laser, characterized in that A laser glass comprising any one of claims 1 to 8.

Citation Information

Cited By

  • Optical glass and optical assembly

    CN121778991A

  • An optical glass and an optical assembly

    CN121778991B